ERBB4 gene polymorphisms and the risk of prostate cancer in a sample of Iranian Population - Hashemi, M; Moradi, N; Rezaei, M; Sanaei, S; Ziaee, S A M; Narouie, B; Sotoudeh, M; Bahari, G; Ghavami, S (Cellular and Molecular Biology, 2016)
Genetic polymorphisms in ERBB4 are thought to be associated with cancer susceptibility. In the present study, we aimed to assess the impact of ERBB4 rs12052398 T>C, rs13393577 A>G, rs13424871 A>T, rs16847082 A>G and rs6147150 (12-bp I/D) polymorphisms on risk of prostate cancer (PCa) in a sample of Iranian population. In a case-control study, we enrolled 169 patients with pathologically confirmed PCa and 182 subjects with benign prostatic hyperplasia (BPH). No significant association was found among ERBB4 polymorphisms and risk of PCa. Subjects carrying TT/AA/AA/AG/ID, TC/AA/AA/AA/II, TT/AA/AT/AA/II and TT/AA/AT/AG/ID genotypes are associated with a decreased risk of PCa. Our findings suggest that haplotypes CAAAI and TAAAD (rs12052398, rs13393577, rs13424871, rs16847082 and rs6147150I) of the ERBB4 polymorphisms are associated with a significantly lower risk of PCa. Further studies with a larger sample sizes and diverse ethnicities are necessary to verify our findings.